2019
DOI: 10.1029/2018rg000615
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Mixing State: Measurements, Modeling, and Impacts

Abstract: Atmospheric aerosols are complex mixtures of different chemical species, and individual particles exist in many different shapes and morphologies. Together, these characteristics contribute to the aerosol mixing state. This review provides an overview of measurement techniques to probe aerosol mixing state, discusses how aerosol mixing state is represented in atmospheric models at different scales, and synthesizes our knowledge of aerosol mixing state's impact on climate‐relevant properties, such as cloud cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
326
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(332 citation statements)
references
References 536 publications
(879 reference statements)
5
326
0
1
Order By: Relevance
“…OM can be divided into primary organic matter (POM) and secondary organic matter (SOM). SOM is produced from the chemical oxidation of volatile organic compounds (VOCs) and often exhibits OM coating on S-rich particles (Li et al, 2016;Moffet et al, 2013;Riemer et al, 2019). Na-rich particles in the marine air are from sea spray and have typical nearcubic shape.…”
Section: Composition and Source Of Aerosol Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…OM can be divided into primary organic matter (POM) and secondary organic matter (SOM). SOM is produced from the chemical oxidation of volatile organic compounds (VOCs) and often exhibits OM coating on S-rich particles (Li et al, 2016;Moffet et al, 2013;Riemer et al, 2019). Na-rich particles in the marine air are from sea spray and have typical nearcubic shape.…”
Section: Composition and Source Of Aerosol Particlesmentioning
confidence: 99%
“…Recently, certain organic aerosols, referred to as brown carbon (BrC), have been recognized as an important light-absorbing carbonaceous aerosol in the troposphere (Alexander et al, 2008;Andreae and Gelencsér, 2006;Feng et al, 2013;Lack et al, 2012). BrC can be directly emitted from combustion sources or form in the atmosphere via photochemical aging (Jiang et al, 2019;Saleh et al, 2013;Updyke et al, 2012). Moreover, aging of secondary organic aerosols can significantly contribute to BrC during atmospheric transport (Laskin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chemistry, transport, and microphysical processes can affect the size and burden of injected aerosols (Riemer et al, 2019). Previous studies have shown that injecting the aerosols at different altitudes in the stratosphere affects the amount of surface cooling in geoengineering experiments (Kleinschmitt et al, 2018;Tilmes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This technique is widespread and has been used in numerous publications (e.g., but not limited to Moore et al, 2010;Padró et al, 2012). The development of a single continuous-flow thermal gradient diffusion column CCN counter, CCNC (Droplet Measurement Technologies, Inc.) has provided rapid (∼ 1 Hz) and robust CCN data (Lance et al, 2013;Roberts and Nenes, 2005). Aerosols with a S c lower than the supersaturation in the column activate and form droplets.…”
Section: Ccn Activity and Chemical Composition: Measurements And Instmentioning
confidence: 99%
“…However, this method of analysis may not be fully representative of the heterogeneous mixing state occasionally present in the aerosol sample. Thus a CCN mixture refers to the diversity of activated aerosols in the particle population (not the property of an individual particle; Winkler, 1973;Riemer et al, 2019).…”
mentioning
confidence: 99%